ISSUES OF CALCULATION AND IMPROVEMENT OF INCOME TAX FROM INDIVIDUALS - Садуллаев Расулбек Палванбаевич (Web of Journals Publishing, 2025)
The article highlights, based on a study of the best practices of foreign countries in improving tax systems, it is necessary to develop a scientific proposal and practical recommendations on ways to improve this tax, taking into account the requirements of the present time.
Keywords: Individuals, personal income tax, state budget, income.